Physiological plasticity of main tree species of lowland hornbeamoak forest as a results of forest gap regeneration - Szalacsi, Árpád; Király, Gergely; Veres, Szilvia (Acta Agraria Debreceniensis, 2016)
Specific leaf area (SLA) of English oak (Quercus robur L.) and hornbeam (Carpinus betulus L.) as members of Querco robori-Carpinetum were investigated in two different habitat in terms of gap forest management: in the gap and in the inert forest. The artificial opening process of the forest resulted in more light for growing saplings and need for acclimatization. Photosynthesis is one of the most important ways for plant life and plant production basically influenced by altered light condition resulted in opening process. Efficient photosynthesis is important for plant life, plant production, but species-dependent plasticity of photosynthesis makes one species more tolerant, than others. The specific leaf area is acceptable parameters for characterising plant production, dry matter content and leaf structure. The dry matter content based on known leaf area is higher in oak both sun and shade leaves, than hornbeam. The different place of leaves in the canopy of trees did not influence the values of SLA.